BS IEC 60966-4-3. Radio frequency and coaxial cable assemblies. Part 4-3. Detail specification for semi-rigid cable assemblies, Frequency range up to 6000MHz, Type 50-12 low loss semi-rigid coaxial cable, applicable to ISO/IEC 11801-1 (15th November 2019) - British Standards Institution,
No abstract available